2002
DOI: 10.1037/0894-4105.16.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Attention, learning, and memory performances and intellectual resources in Vietnam veterans: PTSD and no disorder comparisons.

Abstract: Attention, learning, memory, and estimated intellectual potential were examined in 26 Vietnam veterans diagnosed with posttraumatic stress disorder (PTSD) and in 21 Vietnam veterans without mental disorders. Results revealed PTSD-associated cognitive deficits on tasks of sustained attention, working memory, initial learning, and estimated premorbid intelligence but not on measures of focus of attention, shift of attention, or memory savings. Cognitive task performances adjusted for estimated native intelligenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
373
6
41

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 471 publications
(449 citation statements)
references
References 46 publications
29
373
6
41
Order By: Relevance
“…Two studies found that the relationship between lower IQ and PTSD remained even after controlling for level of combat exposure (Macklin et al, 1998;McNally & Shin, 1995). This relationship between lower IQ and PTSD was supported by subsequent studies with Veterans (Gilbertson, Gurvits, Lasko, Orr, & Pitman, 2001;Vasterling et al, 2002;Gale, Deary, Boyle, Barefoot, Mortensen, & Batty, 2008;Kremen, et al, 2007). Verbal IQ appears particularly sensitive to risk for PTSD (Vasterling, Brailey, Constans, Borges, & Sutker, 1997;;Gil et al, 1990).…”
Section: Neuropsychology Of Ptsdmentioning
confidence: 74%
“…Two studies found that the relationship between lower IQ and PTSD remained even after controlling for level of combat exposure (Macklin et al, 1998;McNally & Shin, 1995). This relationship between lower IQ and PTSD was supported by subsequent studies with Veterans (Gilbertson, Gurvits, Lasko, Orr, & Pitman, 2001;Vasterling et al, 2002;Gale, Deary, Boyle, Barefoot, Mortensen, & Batty, 2008;Kremen, et al, 2007). Verbal IQ appears particularly sensitive to risk for PTSD (Vasterling, Brailey, Constans, Borges, & Sutker, 1997;;Gil et al, 1990).…”
Section: Neuropsychology Of Ptsdmentioning
confidence: 74%
“…PTSD and MTBI patients share a number of similarities in cognitive dysfunction including deficits in attention and difficulties with episodic and working memory. 104,105 These similarities in symptomatology make an accurate diagnosis between MTBI and PTSD difficult. A few MRI studies have reported that patients with PTSD have smaller hippocampal volumes, which could be used for the diagnosis of PTSD.…”
Section: Biomarkers For Differentially Diagnosing Mild Tbi Vs Ptsdmentioning
confidence: 99%
“…One characteristic of PTSD, a hyperarousal state, can affect students with severe emotional tension (Sullivan & Elbogen, 2014) and result in emotional exhaustion. In general, PTSD can give adolescents more cognitive, emotional, and behavioural problems (Husain, Allwood, & Bell, 2008; Vasterling et al, 2002), and all of these factors will increase the probability of adolescent academic burnout.…”
Section: Discussionmentioning
confidence: 99%